The understanding of Norwegian women’s sickness absence: towards a holistic approach? - Liv Johanne Solheim (Nordic Journal of Social Research, 2011)
Background: In Norway men's sickness absence from work has been stable or reduced over the last decades while women's sickness-absence ratio has increased, but the reasons for these developments are complex and unclear. There have been considerable efforts introduced and implemented to reduce sickness absence, but they have not succeeded. One reason for this may be the insufficient knowledge about the reasons for sick leave, and especially for women's sick leave.